Heterotopic Gastric Mucosa in the Proximal Esophagus (Inlet Patch): Endoscopic Prevalence, Clinico-pathological Characteristics and Its Association with Helicobacter pylori - Rathod, Vivek; A., Anand; Ramesh, Nithin Kaidabettu; Shaikh, Mohamed Kani (Journal of Digestive Endoscopy, 2022)
Objective To determine the prevalence of the inlet patch (IP), its clinico-pathological features, and its association with Helicobacter pylori.Materials and Methods A prospective observational study was performed on 1,889 patients referred for esophagogastroduodenoscopy for various reasons, primarily for the evaluation of dyspepsia. All patients were enquired about the presence of symptoms and carefully examined for the presence of IP during upper gastrointestinal (GI) endoscopy. Biopsies were taken from the patients who had IP.Statistical Analysis All statistical analyses were performed using the Statistical Package for Social Sciences (SPSS) 13.0 software for Windows XP. Categorical variables were compared using the chi-squared test or Fisher's exact test and continuous variables were compared using Student's t-test and univariate analysis. A P-value of less than 0.05 was considered to be statistically significant.Results Inlet patches were found in 34 of 1,889 patients (1.8%). H. pylori was identified in 23.52% of patients (8/34) with IP. Gastric H. pylori infection was positive in all (08/08) patients who had IP. Colonization of H. pylori was more common in antral type mucosa (6/8). H. pylori positivity in the IP correlated with globus sensation symptom in our study, 87.5% of patients with IP and H. pylori positive had globus sensation.Conclusion The prevalence of IP seems to be underestimated. H. pylori colonization of the IP is common and it positively correlates with globus sensation and is closely related to the H. pylori density in the stomach. Though preneoplasia within IP is rare, which does not support the recommendation to regularly obtain biopsies for histopathology, it might be beneficial in a subset of patients with persistent globus sensation.
Keywords: cervical heterotopic gastric mucosa; globus sensation; Helicobacter pylori; inlet patch